An Analysis of Code-Switching in English Classroom Interaction at SMP Negeri 10 Medan - Elisabet Butarbutar; Four Maida Manalu (BRIGHT VISION, 2026)
Code-switching is a common phenomenon in English as a Foreign Language (EFL) classrooms where teachers and students alternate between English and Indonesian to support communication and learning. This study investigates the types and functions of code-switching in classroom interaction at SMPN 10 Medan. The objectives of this study are to identify the types of code-switching based on Poplack’s (1980) classification and to analyze its functions based on Appel and Muysken’s (1987) framework. This research employed a qualitative case study design. The data were collected through a 25-minute classroom observation, transcription of teacher-student interaction, and semi-structured interviews with the English teacher. The data were analyzed using Miles, Huberman, and Saldaña’s (2014) interactive model, including data condensation, data display, and conclusion drawing. The findings show that two types of code-switching are dominant in classroom interaction: inter-sentential switching (76.9%) and intra-sentential switching (23.1%), while tag switching appears minimally. Inter-sentential switching is mainly used for clarification of instructions and emotional support, while intra-sentential switching occurs in grammar-related explanations and lexical insertion. In terms of function, referential function is the most dominant, followed by directive, expressive, phatic, and metalinguistic functions. These functions indicate that code-switching is primarily used to facilitate comprehension, manage classroom interaction, reduce student anxiety, and explain grammatical concepts. The results suggest that code-switching is not a language deficiency but a purposeful pedagogical strategy that supports effective teaching and learning in EFL classrooms, particularly at the junior high school level where learners still require linguistic assistance.